Significant photovoltaic enhancement in La-doped BiFeO3 achieved by engineering crystallographic facet arrays. (December 2022) - Liu, Nan; Cao, Yi; Tang, Yun-Long; Zhu, Yin-Lian; Wang, Yu-Jia; Liu, Jia-Qi; Zhang, Heng; Li, Chang-Ji; Zhang, Si-Rui; Yang, Bing; Li, Hai-Ning; Ma, Xiu-Liang
Abstract: Engineering regular surface crystallographic facet arrays on a large scale is useful for tuning and optimizing photophysical properties of optoelectronic materials. Herein, we achieve textured Bi0.5 La0.5 FeO3 (BLFO) film surfaces displaying nanosquare arrays composed of {001} and {110} crystallographic facets, via an effective and controllable thermal etching method. Substantially enhanced photocurrent signals from these faceted samples were confirmed via laser-assisted conductive atomic force microscopy at the nanometer scale, where tens of times increment in photo-generated electric field and short circuit current density were further identified. The electronic structures of the {001} and {110} surfaces were compared by ab-initio calculations, and the conduction band minimum of the latter one shows highly dispersive character thus prompted carrier transport can be anticipated. This thermal etching method provides an efficient strategy for fabricating patterned perovskite films with highly active crystallographic facet arrays and thus will inspire new technological possibilities for high-performance photovoltaic devices. Graphical abstract: Image, graphical abstract .